Analisis Produksi Usahatani Tomat di Kecamatan Telaga Langsat Kabupaten Hulu Sungai Selatan - Desy Issana Sari; Yudi Ferrianta; Rifiana Rifiana (Universitas Lambung Mangkurat, 2013)
The tomato production increases recently because of the rise of its land use This means that tomato become important commodity . The purposes of the study are: (1) to calculate the cost, revenue, income and profit of tomato cultivation; (2) to observe the effect of production factors on tomato yield; (3) to know the price efficiency of input use. The study site was Kecamatan Telaga Langsat, Kabupaten Hulu Sungai Selatan. The doubled linear regression model was used to estimate the effect of inputs on tomato yield. The result shows that the average profit 18 million per hectare. Based on the regression model, the production factor of land, fertil izer, seed, and pesticide have positive and significant impact on tomato yield. However, the use of land and seed is 23. IDR is inefficient, yet.